2021
DOI: 10.1093/jxb/erab141
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of timing of next-generation emergence inAmaranthus hybridusis determined via modulation of seed dormancy by the maternal environment

Abstract: Emergence timing of weed species has critical ecological and agronomical implications. In several species, emergence patterns largely depend on the seedbank dormancy level, which is modulated by specific environmental factors. In addition, environmental conditions during seed maturation on the mother plant have shown marked effects on dormancy level at seed dispersal time. Thus, maternal environment has been suggested to affect seedbank dormancy dynamics and subsequent emergence. However, this modulation has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Our results showed that for this species the changes in the range of temperatures permissive for seed germination were mainly explained by changes in T l(50) , and that the rate at which T l(50) decreased, depended on the stratification temperature. Similar response patterns were found for the spring-summer annuals Polygonum aviculare (Batlla & Benech-Arnold, 2003;Malavert et al, 2017) and Amaranthus hybridus (Fernández Farnocchia et al, 2021). Changes in T l(50) were used to establish a functional relationship between the temperature experienced by the seeds during burial in the soil and the rate of dormancy alleviation to predict the emergence in the field (Figure 5).…”
Section: Discussionmentioning
confidence: 78%
“…Our results showed that for this species the changes in the range of temperatures permissive for seed germination were mainly explained by changes in T l(50) , and that the rate at which T l(50) decreased, depended on the stratification temperature. Similar response patterns were found for the spring-summer annuals Polygonum aviculare (Batlla & Benech-Arnold, 2003;Malavert et al, 2017) and Amaranthus hybridus (Fernández Farnocchia et al, 2021). Changes in T l(50) were used to establish a functional relationship between the temperature experienced by the seeds during burial in the soil and the rate of dormancy alleviation to predict the emergence in the field (Figure 5).…”
Section: Discussionmentioning
confidence: 78%
“…40 µm was observed for the ND brown #1 seeds. In addition to day length also temperature during mother plant reproduction is known to affect coat-imposed dormancy for example of Amaranthus hybridus ( Figure 8D and Fernández Farnocchia et al., 2021 ) and of A. thaliana ( MacGregor et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The life-history strategy of weeds seems to be a blend of phenotypic plasticity and local adaptation for which within-species and within-seedlot variation in seed dormancy depth, as well as variation in dormancy release requirements are key to weed emergence timing ( Baskin and Baskin, 2006 ; Walck et al., 2011 ; Batlla et al., 2020 ). The primary dormancy of freshly harvested mature seeds is established during seed maturation and its depth depends on the environmental conditions during the mother plant’s reproductive growth ( Karssen, 1970 ; Penfield and MacGregor, 2017 ; Fernández Farnocchia et al., 2021 ). The control of germination by dormancy can be considered as block(s) to the completion of germination of an intact viable seed under otherwise favorable conditions, namely when the seed becomes non-dormant ( Finch-Savage and Leubner-Metzger, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…arabicum fruit and seed morphs ( Lenser et al ., 2016 ). Temperature and photoperiod contribute to population fitness by affecting seed coat cell wall properties (thickness, proanthocyanidin content) and thereby dormancy in other species ( Finch-Savage et al , 2006 ; Mizzotti et al , 2014 ; MacGregor et al , 2015 ; Fernández Farnocchia et al , 2021 ). The cell wall is a highly dynamic and adjustable structure, and its biomechanical properties are determined by specific cell wall compositions for which new modelling approaches are being pursued (B.…”
mentioning
confidence: 99%